An outcome evaluation of the Work 4 Progress Programme for unemployed youths - Pophiwa, Pamela (College of Accounting, 2024)
This evaluation assessed whether the Work 4 Progress programme, a youth employment programme implemented by Action Volunteers Africa achieved its intended short-term and long-term outcomes. The programme is designed to improve the employability of young people aged between 18 to 25 years who are not in employment, education or training (NEET), by providing them with work opportunities, life coaching and career guidance. The evaluation used a mixed-method exploratory sequential design to collect data. To measure the outcomes of the programme, 29 alumni completed an online survey designed to assess their attainment of the programme outcomes namely: work-related skills and competencies; personal growth and career orientation. Eight participants also took part in semi-structured face-to-face interviews with the evaluator. The programme's Executive Director was also interviewed to promote triangulation of the results. Results of the analysis of the survey data revealed that the Work 4 Progress programme is likely to improve the employability of youths and the participants were overall satisfied with the experience. Results from the analysis of interview data revealed three overall themes. The emerging themes were: 1) Understanding backgrounds, 2) Career guidance is crucial and useful and 3) Programme praxis and knowledge in the real world. Overall, the informants felt that the programme equipped them with the skills and competencies needed in the world of work. The triangulation of the quantitative and qualitative results revealed both the economic and social benefits of engaging in the Work 4 Progress programme. The findings of this evaluation reinforce the importance of multi-component interventions as essential in improving the employment outcomes of youths with socio-economic disadvantages.